Efektivitas Pelayanan Publik Program Mobile Customer Service on Call (MCS-OC) pada Badan Penyelenggaraan Jaminan Sosial Kesehatan Kota Jambi - Nuraini Nuraini; Mhd Ansori; Gebi Chica Lorenza (Universitas Batanghari Jambi, 2021)
This study aims to identify and analyze the influencing factors, constraints and solutions, as well as the effectiveness of public services for the Mobile Customer Service On Call (MCS-OC) program at the Jambi City organizer of the health social security (BPJS). The research method used is juridical empirical research, research which is carried out on existing legal facts by making direct observations in the field in order to determine the implementation and any matters that arise and are adjusted to the laws and regulations. Based on the results of the research, it is known that the effectiveness of public services for the Mobile Customer Service On Call (MCS-OC) program at the Jambi City organizer of the health social security (BPJS) is quite effective because it has achieved all the factors that measure the effectiveness of services and the information obtained.